RESISTANCE TO STEM NECROSIS DISEASE IN INDIGENOUS POTATO GERMPLASM - Somani, Ashok Kumar (Potato Journal, 2018)
Indigenous germplasm accessions of potato (Solanum tuberosum L.) numbering 121 were continuously screened for three seasons against stem necrosis disease caused by groundnut bud necrosis virus transmitted through thrips which is a serious problem in early planted crops.  Of the 121 germplasm, 13 were found to be highly resistant, 15 resistant, 23 moderately resistant, 35 each were susceptible and highly susceptible.  The 10 highly resistant accessions were; CP-1878 (Mahabaleshwar Red) , CP-2142 (Kufri Dewa),  CP-3786 (SM/88-991),   NJ-1,  NJ-40,  NJ-44,  NJ-64,  NJ-66,  NJ-75,  NJ-82, 92/51(J),  G-2524 and  PS/M.98.